Gangrenous appendicitis contained within a Spigelian hernia. Issue 1 (2nd January 2021) - Anand, Rohan; Rahesh, Jasmin; Ciubuc, John; Esparza-Leal, Karla; Schuster, Abbie; Jacob, Roy; Brooks, Steven E.; Richmond, Robyn; Ronaghan, Catherine A.
Abstract: A 66-year-old man with abdominal pain had a 5-year-old mass subsequently identified as a Spigelian hernia. Exploratory laparotomy revealed a strangulated and gangrenous appendix contained within the hernia, necessitating an appendectomy. This case highlights the importance of early identification and exploration of this rare hernia, so that early management can prevent the development of more serious and dangerous symptoms.